2022
DOI: 10.1021/acs.macromol.1c02432
|View full text |Cite
|
Sign up to set email alerts
|

Imine-Based Reactive Mesogen and Its Corresponding Exchangeable Liquid Crystal Elastomer

Abstract: To date, exchangeable liquid crystalline elastomers (xLCEs) have been mainly fabricated by combining conventional LCEs with additional exchangeable functional groups in their networks. While conventional LCEs are frequently made from commercially available aromatic–ester reacting mesogens or from mesogens based on a biphenyl core, such reacting monomers are not optimized to fabricating xLCEs whose bond-exchange reaction is fast and clean cut. Here, we develop a fast synthesis route to produce a new type of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…In recent years, the concept of adaptivity has gained broad attention for the development of new functional materials as it allows the controlled manipulation of materials properties. With respect to this, dynamic covalent chemistry (DCC) bears great potential as it combines the error-correction capability and adaptivity of supramolecular chemistry with the robustness of the covalent bond. Regarding the formation of functional systems, such as molecular cages and macrocycles, significant progress has been achieved, and also first steps toward the application in materials were reported. , So far, DCC was mainly used to manipulate the properties of liquid crystalline elastomers (LCEs). An interesting example was presented by Mulder et al, who reported the fabrication of nanoporous liquid crystalline networks using the dynamics of imine bonds to manipulate the pore size and functionality of their materials . However, reports on low-molecular-weight liquid crystals based on DCC are rare. An interesting example was reported in 2006 by Giuseppone and Lehn.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the concept of adaptivity has gained broad attention for the development of new functional materials as it allows the controlled manipulation of materials properties. With respect to this, dynamic covalent chemistry (DCC) bears great potential as it combines the error-correction capability and adaptivity of supramolecular chemistry with the robustness of the covalent bond. Regarding the formation of functional systems, such as molecular cages and macrocycles, significant progress has been achieved, and also first steps toward the application in materials were reported. , So far, DCC was mainly used to manipulate the properties of liquid crystalline elastomers (LCEs). An interesting example was presented by Mulder et al, who reported the fabrication of nanoporous liquid crystalline networks using the dynamics of imine bonds to manipulate the pore size and functionality of their materials . However, reports on low-molecular-weight liquid crystals based on DCC are rare. An interesting example was reported in 2006 by Giuseppone and Lehn.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a slow creep under load was performed to align an LCE film in the nematic phase because it exhibited a fast imine metathesis reaction. [74] The introduction of permanent crosslinking moieties allowed controlling plasticity in the nematic phase while avoiding a large creep caused by the presence of fast boronic ester reactions. [75] Although the programming of DCB-based LCEs in the LC phase appears to be detrimental due to loss of thermal and actuation stability, this is advantageous when thermally activated DCBs are incorporated into phototropic LCEs, as it allows orthogonal stimuli to induce reprogramming of deformation modes and retention of actuated states via bond exchange.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Although the xLCE film was shown to exhibit thermally reversible action, the rapid dynamic exchange hindered proper isotropic-genesis programming and thus limited thermal stability upon heating/cooling cycles above T i (70 °C). [74] 3.6. Urethane and thiourea bond exchange…”
Section: Imine Bond Exchangementioning
confidence: 99%
See 2 more Smart Citations